An interactive visiting system using BLE devices - Garrido, N.; Serrão, C.; Coitos, B. (Internet of things: cases and studies, 2021)
This chapter presents a use case based on the development of an interactive, integrated and adaptable visiting system for complex buildings and surrounding grounds (smart places). The system features a mobile application that allows the user to access information from several smart places in a single application, and an Indoor Location and Tracking System that infers the user location during the smart place visit. The system calculates the tracking and location of the user based on the positioning of neighbouring BLE devices sensed via Bluetooth on the user’s mobile device. The approximate location, behaviour and interests, and hence the visiting profile of each user, can be inferred by the signals from multiple beacons installed on the building at specific pre-defined positions. The system also integrates a backend content management system to allow the creation and management of smart places information and supports information import from BIM tools.